2015
DOI: 10.5487/tr.2015.31.1.069
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Oral Dose Toxicity of Freeze-dried Powder of Allomyrina dichotoma Larvae

Abstract: The objective of this study was to investigate the toxicological information of freeze-dried powder from Allomyrina dichotoma (A. dichotoma) larvae as a food ingredient. The powder, suspended in distilled water, was administered once daily by oral gavage to four groups of Sprague-Dawley (SD) rats at dose levels of 0 (vehicle control), 250, 850, and 2500 mg/kg/day. After 13 wks of repeated administration, the standard toxicological parameters such as mortality, clinical signs, body weight, food consumption, oph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…An evaluation of the safety of T. molitor larvae as a food ingredient revealed no adverse effect or toxicity in Sprague-Dawley (SD) rats after 90 days of administration at a maximum concentration of 3000 mg/kg/day [18]. Other edible insects Allomyrina dichotoma (Coleoptera: Scrabaeidae) revealed no adverse effect for 13 weeks (NOAEL: 2500 mg/kg/day) in SD rats [19], and subacute oral toxicity with Gryllus bimaculatus (Orthoptera: Gryllidae) for 4 weeks in SD rats were performed, and no toxicity were observed (NOAEL: 3000 mg/kg/day) [20]. Recently, Z. atratus has been recognized as a temporary food ingredient through the evaluation of suitability and food safety of manufacturing methods by the Korea Ministry of Food and Drug Safety (MFDS) in January 2020.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of the safety of T. molitor larvae as a food ingredient revealed no adverse effect or toxicity in Sprague-Dawley (SD) rats after 90 days of administration at a maximum concentration of 3000 mg/kg/day [18]. Other edible insects Allomyrina dichotoma (Coleoptera: Scrabaeidae) revealed no adverse effect for 13 weeks (NOAEL: 2500 mg/kg/day) in SD rats [19], and subacute oral toxicity with Gryllus bimaculatus (Orthoptera: Gryllidae) for 4 weeks in SD rats were performed, and no toxicity were observed (NOAEL: 3000 mg/kg/day) [20]. Recently, Z. atratus has been recognized as a temporary food ingredient through the evaluation of suitability and food safety of manufacturing methods by the Korea Ministry of Food and Drug Safety (MFDS) in January 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of ADE was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay after treatment with various concentrations of ADE (0.01–5 mg/mL). As a result, up to 5 mg/mL of ADE showed no cytotoxic effect on hypothalamic neuronal GT1-7 cells [ 17 ]. To determine whether or not central administration of ADE regulates food intake and body weight in high-fat-diet-induced mice, we administrated a single dose of ADE (1 μL of 10 mg/mL ADE) into the third ventricle.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some safety evaluations conducted in this study were performed to according to international test guidelines ( OECD, 2008 ). In the aforementioned studies, no toxicity was observed with the consumption of T. molitor at a dose of <3,000 mg/kg/d ( Han et al, 2014 ); A. dichotoma at 2,500 mg/kg/day ( Noh et al, 2015 ); and G. bimaculatus at less than 1,000 mg/kg/day ( Noh et al, 2015 ). T. molitor and A. dichotoma were confirmed to be associated with subchronic oral dose toxicity for 90 days in 5-week-old SD rats ( Han et al, 2014 ; Noh et al, 2015 ), and G. bimaculatus was confirmed to be associated with subacute oral dose toxicity for 28 days with 5-week-old SD rats ( Lee et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several attempts have been made to identify various insect resources as useful biological resources and utilize them for different purposes. According to the Food and Agriculture Organization (FAO), two billion people worldwide consume insects and the use of insects as food will provide economic benefits when insects are used as a substitute for animal protein ( Noh et al., 2015 ). However, it is important to establish the safety of insects for human consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation